Jasmonic acid‐dependent regulation of seed dormancy following maternal herbivory in Arabidopsis. Issue 4 (23rd March 2017) - Singh, Prashant; Dave, Anuja; Vaistij, Fabian E.; Worrall, Dawn; Holroyd, Geoff H.; Wells, Jonathan G.; Kaminski, Filip; Graham, Ian A.; Roberts, Michael R.
Summary: Maternal experience of abiotic environmental factors such as temperature and light are well known to control seed dormancy in many plant species. Maternal biotic stress alters offspring defence phenotypes, but whether it also affects seed dormancy remains unexplored. We exposed Arabidopsis thaliana plants to herbivory and investigated plasticity in germination and defence phenotypes in their offspring, along with the roles of phytohormone signalling in regulating maternal effects. Maternal herbivory resulted in the accumulation of jasmonic acid‐isoleucine and loss of dormancy in seeds of stressed plants. Dormancy was also reduced by engineering seed‐specific accumulation of jasmonic acid in transgenic plants. Loss of dormancy was dependent on an intact jasmonate signalling pathway and was associated with increased gibberellin content and reduced abscisic acid sensitivity during germination. Altered dormancy was only observed in the first generation following herbivory, whereas defence priming was maintained for at least two generations. Herbivory generates a jasmonic acid‐dependent reduction in seed dormancy, mediated by alteration of gibberellin and abscisic acid signalling. This is a direct maternal effect, operating independently from transgenerational herbivore resistance priming.